Under my hijab [book with audioplayer] - Khan, Hena ([Library Ideas, LLC], 2021)
Grandma wears it clasped under her chin. Aunty pins hers up with a beautiful brooch. Jenna puts it under a sun hat when she hikes. Zara styles hers to match her outfit. As a young girl observes six very different women in her life who each wear the hijab in a unique way, she also dreams of the rich possibilities of her own future, and how she will express her own personality through her hijab. Written in sprightly rhyme and illustrated by a talented newcomer, Under My Hijab honors the diverse lives of contemporary Muslim women and girls, their love for each other, and their pride in their culture and faith.